Institutional Disability : the saga of transportation policy for the disabled - Katzmann, Robert A. (Washington, D.C. : The Brookings Institution, 1986)
In this book, the author examines the workings of the legislative, administrative, and judicial processes, both separately and in interaction, as he relates the erratic path of transportation policy for the disabled over two decades.
Includes bibliographical references and index.
ne 08/06/2018
Loans
Keywords: People with disabilities